Dissociative recombination of vibrationally excited HD+: state-selective experimental investigation - Amitay, Zohar; Baer, A.; Dahan, M.; Levin, J.; Vager, Z.; Zajfman, D.; Knoll, L.; Lange, Michael; Schwalm, Dirk; Wester, Roland; Wolf, Andreas; Schneider, I. F.; et al. (Physical review. A, Atomic, molecular, and optical physics, 1999)
The relative dissociative recombination rate coefficients for specific vibrational states of HD+ have been measured. The method is based on using merged electron and molecular ion beams in a heavy-ion storage ring together with molecular fragment imaging techniques which allow us to probe the vibrational-state population of the stored beam as a function of time as well as the final state of the dissociation. The initial vibrational distribution of the stored ion beam (from a Penning ion source) is found to be in good agreement with a Franck-Condon model of electron impact ionization, apart from slightly larger experimental populations found for low vibrational states; its time evolution in the storage ring reflects the predicted vibrational level lifetimes. Dissociative recombination measurements were performed with the electron and ion beams at matched velocities (corresponding to average collision energies of about 10 meV), and at several well-defined collision energies in the range of 3-11 eV. The obtained vibrational-state specific recombination rate coefficients are compared with theoretical calculations and show that, although an overall agreement exists between experiment and theory, large discrepancies occur for certain vibrational states at low electron energy.
Gesehen am 30.11.2020
Im Titel ist das Pluszeichen hochgestellt